EFEKTIFITAS TERAPI HIPNOTIS LIMA JARI TERHADAP TINGKAT KECEMASAN PADA MAHASISWA YANG AKAN MENGHADAPI UJIAN UKOM - LINDA ANDRIANI; LARASUCI ARINI; LEVINA NUR DIANSYAH (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2026)
Anxiety before the Competency Examination (UKOM) is a common psychological issue among health students that can reduce concentration, self-confidence, and exam performance. One effective non-pharmacological approach to manage anxiety is five-finger hypnosis therapy, a simple self-relaxation technique combining positive suggestions and focused concentration. This study aimed to determine the effectiveness of five-finger hypnosis therapy in reducing anxiety levels among students preparing for the UKOM at STIKes Piala Sakti Pariaman. A pre-experimental design with a one-group pretest-posttest approach was employed. The sample consisted of 20 students selected through purposive sampling. Data were collected using a standardized anxiety questionnaire and analyzed with a paired sample t-test. The results showed a significant decrease in anxiety after the intervention. The mean anxiety score before therapy was 68.75 and decreased to 34.15 after therapy, with a mean difference of 34.60 and a p-value of 0.000 (p < 0.05). The number of students with no anxiety increased from 55% to 85%. These findings indicate that five-finger hypnosis therapy effectively reduces pre-exam anxiety. Therefore, it is recommended that this method be implemented as a simple, practical, and independent relaxation technique to support students’ mental readiness before competency examinations. Keywords: Five-finger hypnosis, anxiety, UKOM